Association of Neonate’s Birth Weight with Material Weight Gain during Pregnancy - Jabeen, Syeda Surayya; Iffet, Shazia; Imtiaz, Umber; Mumtaz, Faria; Sultana, Bushra; Arif, Ayesha (Journal of Rawalpindi Medical College, 2024)
Objective: To establish a relationship between maternal weight gain during pregnancy and a newborn’s birth weight. Method: A total of 120 patients were selected for this study. The weight and height of all patients were recorded in the first month of pregnancy and at term. Weight gain during pregnancy was placed in three categories. Category 1,2 and 3 included patients with weight gain of 4.9 kg or less, weight gain between 5 to 10 Kg and weight gain over 10 kg respectively. The weight of all newborns was also recorded. The association of maternal weight gain with neonate’s birth weight was looked for. Results: In our study, 4.16% of women were underweight, 49.17% of women were labelled normal weight, 45% were overweight and 2% were obese. Five per cent of women gained less than 5 kg weight during pregnancy, the majority (88.33%) gained between 5 to 10 kg and only 8% gained weight more than 10 kg. In our study, 9.17% of newborns were born with low birth weight, 90.83% had normal birth weight and no newborn fell into the category of macrosomia. Mean birth weight was 2.52±0.26 kg in mothers who gained less than 5 kg weight during pregnancy. Similarly, the mean birth weight was 2.92±0.23 in mothers who gained weight between 5 to 10 kg. Mean birth weight was 3.34±0.23 in mothers who gained weight more than 10 kg. Conclusion: It is concluded in our study that maternal weight gain during pregnancy is strongly associated with the birth weight of the newborn. Keywords: Birth weight, Gestational weight gain, Neonatal birth weight, Maternal weight gain.